Integrasi Pendidikan Agama Hindu Dalam Pembelajaran Bahasa Sanskerta Pada Yayasan Dvīpāntara Saṁskrtam - Gede Agus Siswadi; Kadek Aria Prima Dewi PF; I Made Arsa Wiguna (Jayapangus Press, 2019)
Hindu religious education which has been carried out in the realm of formal, non-formal and informal education. The Dvipantara Samskrtam Foundation which is a non-formal education institution is able to integrate Hindu religious education with Sanskrit learning, not only in the cognitive domain, but also in the affective and psychomotor domains. There are a number of problems to be discussed in this study: 1) What is the form of Sanskrit learning at the Dvipantara Samskrtam Foundation? 2) What problems are faced in learning Sanskrit on the Dvipantara Samskrtam Foundation? Sanskrit in the Dvipantara Samskrtam Foundation. The results of this study indicate: 1) The form of Sanskrit learning in the Dvipantara Samskrtam Foundation can be seen in terms of the learning process, which includes a learning approach using socio-emotional approaches, active learning interactions from educators, students, students and students educators, components in the interaction of learning by using media images, hand gestures, using direct learning models (direct instruction), 2) Problems faced include factors such as perception, attitude, and motivation, while external factors include educators, climate learning, and infrastructure. 3) Integration of Hindu religious education in Sanskrit learning on the Dvipantara Samskrtam Foundation includes: cognitive, affective domains, and psychomotor domains.